The effect of mulch on properties of erosion sensitive soil using a wind tunnel - P. Gholamiderami; P. Lahooti; H. Darbam (Global Journal of Environmental Science and Management)
The aim of this study was to produce mulch by combining natural mineral and organic substances in order to reach soil stabilization and improve soil physical and mechanical properties in Koopal area. The effects of organic mulch (at 3 levels of O1: combination of 1% sugarcane bagasse biochar+0.5% gum Arabic+0.5% gelatin; O2: combination of 3% sugarcane bagasse biochar+1% gum Arabic+1% gelatin; and O3: combination of 5% sugarcane bagasse biochar+1.5% gum Arabic+ 1.5% gelatin) and MNF organomineral mulch (at 3 levels of MNF1: 1%; MNF2: 3%; and MNF3: 5%) on soil were investigated. The soil samples were incubated for 2 and 4 months and finally placed in a wind tunnel. Some physical and chemical properties of soil were obtained as pH=7.42, O.M%=0.223, and soil texture of silty loam. The obtained results showed that compared to control, application of the mulches increased soil organic carbon percentage (1.1%), mean weight diameter (2.47 mm), geometric mean diameter (1.27 mm), penetration resistance (370), shear strength (27.38) and tensile strength (0.8) significantly and decreased soil loss (0.10 g/m2/s), fracture index, soil texture index (62.16), and crust index (1.18) significantly (P<0.01) in both incubation periods. Effects of the mulches on soil organic carbon were reduced after 4 months. In mulch treatments, soil loss rate, mean weight diameter, geometric mean diameter and tensile strength were increased significantly. In general, the organic mulch could stabilize the soil and improve the physical and mechanical properties of the soil.